Enhancing Environmental Awareness Among Entrepreneurs and Digital-Based Marketing Mechanisms for MSME Products - SELAMET, I Ketut; LAKSMI, Putu Ayu Sita; SAPUTRA, Komang Adi Kurniawan; PUTRA, I Komang (Community Services: Sustainability Development, 2024)
Environmental awareness among MSME actors in the Dauh Puri Kangin Village area is important to consider as it can positively impact the environment and public health. Here are some key points regarding the environmental awareness of MSME actors: 1. Applying business environmental ethics can reduce the negative impact of MSME production and create business sustainability. 2. Understanding and awareness among MSME actors are necessary for waste management. 3. The government needs to assist MSMEs by facilitating waste management, such as ensuring the operation of wastewater treatment facilities. In addition to environmental awareness, MSME actors also need to pay attention to other issues, such as limited business capital, licensing problems, financial management, lack of product innovation, and difficulties in business development. Digital marketing mechanisms for MSMEs in the Dauh Puri Kangin Village area can be implemented using digital technology and online platforms to achieve marketing goals. Some digital marketing strategies that MSMEs can adopt include: 1. MSMEs can create their own sales website to design the layout, ambience, product catalogue, and promotions. The website should be mobile-friendly for easy access via smartphones. 2. MSMEs can leverage social media as a promotional tool for sales. They can create special groups on platforms like WhatsApp and Line to send product catalogues to loyal customers. 3. MSMEs can collaborate with marketplaces to sell their products. Marketplaces like Shopee and Tokopedia provide security for MSMEs regarding payments. 4. MSMEs can implement email marketing as an online marketing strategy. 5. MSMEs can provide responsive and effective customer service through digital channels such as email, social media, and online chat. Important principles in digital marketing include understanding the target market and consumer behaviour in the digital space, identifying digital platforms that align with the target audience, and analyzing data to measure marketing performance.